Analysis of Regional Financial Performance of Batu City during the Covid Pandemic Transition 19 - Alif Dewantara; Arif Dwi Hartanto (Innovation Business Management and Accounting Journal, 2024)
This study aims to see how the financial performance of the stone city region after the transition of the covid 19 pandemic where this type of research is descriptive quantitative research and the sample used is data on the realization of the stone city APBD for 2020-2022 which can be obtained at DJPK using 3 regional financial ratios the results show that the ratio of the degree of destructiveness is still very low, meaning that the ability of the region in regional autonomy is very small. role, while the results of the regional financial independence ratio are still consultative in nature, meaning that the role of the central government has been reduced but needs to be increased so that participatory development is achieved, finally the results of the effectiveness of PAD are still less effective in exploring the potential of PAD where the ratio has not exceeded 100%.